2009
DOI: 10.1136/bmj.b3928
|View full text |Cite
|
Sign up to set email alerts
|

Partial protection of seasonal trivalent inactivated vaccine against novel pandemic influenza A/H1N1 2009: case-control study in Mexico City

Abstract: Objective To evaluate the association of 2008-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 18 publications
10
89
2
5
Order By: Relevance
“…infection with influenza A(H1N1)pdm09 is uncertain, and a range of estimates have been made, which range from indicating protection, [10][11][12][13] to no effect, [14][15][16][17][18][19][20][21][22][23] to increased susceptibility. [24][25][26] A recent meta-analysis found that prior receipt of seasonal influenza vaccination may have been associated with moderate protection against influenza A(H1N1)pdm09.…”
Section: Resultsmentioning
confidence: 99%
“…infection with influenza A(H1N1)pdm09 is uncertain, and a range of estimates have been made, which range from indicating protection, [10][11][12][13] to no effect, [14][15][16][17][18][19][20][21][22][23] to increased susceptibility. [24][25][26] A recent meta-analysis found that prior receipt of seasonal influenza vaccination may have been associated with moderate protection against influenza A(H1N1)pdm09.…”
Section: Resultsmentioning
confidence: 99%
“…We designed this study in mice to examine the contribution of prior exposure to seasonal influenza vaccination or infection to the immune response to and efficacy of a 2009 p-H1N1 vaccine (6,(12)(13)(14)(15)(16). We focused on p-LAIV rather than the inactivated pandemic vaccine because the breadth of the immune responses induced by LAIV in naïve mice is greater than inactivated vaccine (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies conducted in the United States and Australia, prior seasonal influenza vaccination did not have a significant effect on the incidence of p-H1N1 infection (6,12). In contrast, in a small retrospective case-control study in Mexico, more severe clinical outcomes were noted among individuals infected with the p-H1N1 virus who had not been previously vaccinated with the 2008-2009 seasonal influenza vaccine (13). Another retrospective analysis in Mexico also noted a lowered risk of p-H1N1 infection among individuals who had been vaccinated with seasonal influenza vaccine (14).…”
mentioning
confidence: 96%
“…These findings suggest that vaccination with seasonal influenza vaccines might still be of benefit in this pandemic, at least in some cases, in terms of the induction of cross-reactive CTLs. Indeed, recent epidemiological studies also showed that seasonal trivalent inactivated influenza vaccine (TIV) could provide some protection (16,19), although the seasonal influenza vaccine does not stimulate protective antibody responses to pdmH1N1.…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 99%